2020
DOI: 10.7717/peerj-pchem.12
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation kinetics of binary systems containing kaolinite and Pseudomonas putida induced by different 1:1 electrolytes: specific ion effects

Abstract: Background The interactions between colloidal particles in the binary systems or mixture colloids containing clay minerals and bacteria have important influences on formations and stabilities of soil aggregates, transportations of soil water, as well as biological activities of microorganisms. How the interfacial reaction of metal ions affects their interaction therefore becomes an important scientific issue. Methods Dynamic light scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…According to the aggregation theory, for either a single or mixture system, a given CCC value means a given vfalse˜T()f0~ f 0 linear relationship, and thus the electrostatic potential energy and van der Waals potential energy are given, based on Equation (). Indeed, many studies have shown that, for clays, humus, microbes, a clay‐humus mixture, a clay microbe mixture and even for soil of a complex mixture, just one CCC could be observed (Gao et al, 2015; Gao, Li, Tian, Liu, & Zhu, 2014; Jia et al, 2013; Yu, Tian, Liu, Zhang, & Li, 2020). This implies that our suggested theory and the DLS technique are applicable to both single and mixed systems with different colloidal materials for the van der Waals potential energy determination.…”
Section: Theorymentioning
confidence: 99%
“…According to the aggregation theory, for either a single or mixture system, a given CCC value means a given vfalse˜T()f0~ f 0 linear relationship, and thus the electrostatic potential energy and van der Waals potential energy are given, based on Equation (). Indeed, many studies have shown that, for clays, humus, microbes, a clay‐humus mixture, a clay microbe mixture and even for soil of a complex mixture, just one CCC could be observed (Gao et al, 2015; Gao, Li, Tian, Liu, & Zhu, 2014; Jia et al, 2013; Yu, Tian, Liu, Zhang, & Li, 2020). This implies that our suggested theory and the DLS technique are applicable to both single and mixed systems with different colloidal materials for the van der Waals potential energy determination.…”
Section: Theorymentioning
confidence: 99%
“…Similarly altering the surface hydrophobicity can bring about a difference in adsorption. Thus by changing one or more of the surface properties of the interacting surfaces, adsorption can be made more selective (Jiang et al, 2016;Attwood et al, 2019;Boudjema et al, 2020;Yu et al, 2020).…”
Section: Zeta Potential Of Single Mineralsmentioning
confidence: 99%